Strategic HR?: a study of the perceived role of HRM departments in Brazil and Peru - Coda, Roberto; Roux Valentini Coelho César, Ana Maria; Bido, Diógenes de Souza; Louffat, Enrique (Associação Nacional de Pós-Graduação e Pesquisa em Administração, 2009)
This study discusses the perceived role of the Human Resource Management Department and its perceived capacity of outstanding performance by comparing data collected in Brazil and Peru from employees of large organizations as well as participants in MBA programs at renowned schools. The non-probabilistic sample was composed of 416 Brazilian and 90 Peruvian respondents. The results point out that both in Brazil and Peru, the relevance attached to the HRM Department role for contributing to the future success of organizations does not correspond to its current capacity of performance. As such, in these realities the HRM Department has not yet made the qualitative leap that would enable its strategic role in organizations.
Keywords: HRM department performance; Human resource policies; Desempeño del departamento de gestión de recursos humanos; Políticas de recursos humanos; HRM role effectiveness; Efectividad del rol de gestión de recursos humanos; https://purl.org/pe-repo/ocde/ford#5.02.04